Influência de fatores abióticos na composição das comunidades de girinos em ambientes potencialmente salobros - Conceição, Lennise Costa (2023)
The morphophysiological characteristics of anuran larvae make this taxonomic group a model for studies of environmental disturbances, as many physicochemical factors can influence the ontogenetic development, diversity, richness and abundance of individuals. The present study aimed to investigate which physicochemical factors influence the richness and abundance of tadpole communities in an estuary region in the central portion of the Atlantic Forest. To this end, samples were collected in 21 temporary puddles in the municipality of Jaguaripe, Bahia. 45 species of anurans were collected, 15 only in the adult phase, 20 in both phases and 10 only in the larval phase, totaling 45 species belonging to 7 families. Scinax x-signatus occurred in 80.95% of the pools and was also the most abundant, while Physalaemus cuvieri and Scinax group ruber were the least abundant. Among the environmental variables, area, pH and temperature were those that best explained the distribution of species throughout the pool. Pools with lower pH values showed greater richness, while pools with larger areas and temperatures showed greater abundance and lower richness. The variables pH, temperature and salinity directly affect the development and metamorphosis of tadpoles, while the size of water bodies can influence interspecific relationships in the microhabitat and spatial distribution of these organisms. Investigations that take into account the effect of global warming on the physicochemical parameters of water bodies can help to understand how anurans will be affected by climate change.